Plugging material, its preparation method and application

CN117946321BActive Publication Date: 2026-10-20CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211366131.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-31
Publication Date
2026-10-20
Estimated Expiration
2042-10-31

AI Technical Summary

Technical Problem

[0005]本发明的目的是为了克服现有技术存在的由于在胶乳中加入盐引起胶乳凝固而导致残留的阳离子对破乳后的材料性能有较大影响,并且对封堵尺寸有一定限制,且无法深入裂隙的问题,提供一种堵漏材料及其制备方法和应用,该堵漏材料避免了残留的阳离子对破乳后材料性能的影响,可封堵不同尺寸井漏,且更加适合需要深入裂隙的钻完井堵漏需求

Benefits of technology

(1)本发明提供一种智能压敏堵漏材料,在不漏失情况下保持流动状态,遇到漏失情况在压力差作用下启动封堵作用,实现随漏随堵,不漏不堵的智能化堵漏。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the field of drilling and completion plugging, and discloses a plugging material, a preparation method and application thereof.The plugging material comprises the following components: latex, latex prepolymer, surfactant, stabilizer and water, wherein the stabilizer is a compound with cross-linkable groups and / or couplable groups.The plugging material provided by the present application expands the plugging size compared with the latex demulsification type material, and can penetrate into fissures compared with the traditional high fluid loss material, and is more suitable for plugging requirements.The plugging material provided by the present application is applied to the field of oil and gas wells, and can be used in combination with bridging materials to plug different sizes of well leakage, thereby providing a new intelligent material for the field of drilling and completion plugging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wellbore sealing, specifically to a sealing material, its preparation method, and its application. Background Technology

[0002] Drilling well leakage is a phenomenon in which a large amount of drilling fluid leaks into the formation being drilled during the drilling process.

[0003] Existing technologies involve adding salt to latex to cause it to coagulate. The residual cations have a significant impact on the material properties after demulsification, and also limit the sealing size and cannot penetrate deep into cracks.

[0004] Therefore, a new drilling plugging material is needed. Summary of the Invention

[0005] The purpose of this invention is to overcome the problems of existing technologies where the addition of salt to latex causes latex coagulation, resulting in residual cations that significantly affect the material properties after demulsification, and also limits the sealing size and the ability to penetrate deep into fractures. This invention provides a plugging material, its preparation method, and its application. This plugging material avoids the influence of residual cations on the material properties after demulsification, can seal well leaks of different sizes, and is more suitable for well completion plugging needs that require deep penetration into fractures.

[0006] To achieve the above objectives, a first aspect of the present invention provides a sealing material comprising the following components: latex, latex prepolymer, surfactant, stabilizer, and water, wherein the stabilizer is a compound having crosslinkable groups and / or coupling groups.

[0007] A second aspect of the present invention provides a method for preparing a leak-sealing material provided by the present invention. The method includes: first mixing latex, surfactant and water, then mixing with a stabilizer, and finally mixing with a latex prepolymer to obtain the leak-sealing material.

[0008] The third aspect of the present invention provides the application of the plugging material provided by the present invention or the plugging material prepared by the preparation method provided by the present invention in oil reservoir plugging.

[0009] The beneficial effects of the present invention through the above technical solution are: (1) The present invention provides an intelligent pressure-sensitive sealing material that maintains a flowing state when there is no leakage, and activates the sealing function under the action of pressure difference when there is leakage, so as to realize intelligent sealing when there is leakage and not sealing when there is no leakage.

[0010] (2) A novel demulsification mechanism is adopted, namely, the latex stabilizer aggregates and crosslinks under pressure difference, thus failing and leading to latex demulsification. Furthermore, the crosslinking groups used have a beneficial effect on the properties of the resulting plugging solid material, such as viscosity and mechanical strength, and avoid the influence of metal cations on rubber properties after salt demulsification. The plugging material provided by this invention provides excellent sealing for sand beds and can withstand pressures greater than 12 MPa at 90°C.

[0011] (3) The sealing process of the material is controlled into two stages: thickening and solidification. Changing the rheological properties of the fluid instead of directly solidifying the process gives the sealing fluid the opportunity to penetrate deep into the crack, avoiding "sealing the door" type of sealing, which is more suitable for the sealing needs of well leakage after drilling.

[0012] (4) The intelligent pressure-sensitive plugging material, in combination with the bridging material, can seal well leaks of different sizes, providing a new intelligent material for well completion plugging. The plugging material provided by this invention, in combination with the bridging material, plays a good role in sealing 1mm sealing plate modules, and can withstand pressure greater than 12MPa at 100℃. Detailed Implementation

[0013] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0014] The first aspect of the present invention provides a sealing material comprising the following components: latex, latex prepolymer, surfactant, stabilizer and water, wherein the stabilizer is a compound having crosslinkable groups and / or coupling groups.

[0015] The plugging material provided by this invention employs a novel demulsification mechanism. It maintains a fluid state when there is no leakage. In the event of leakage, the stabilizer dehydrates and aggregates under pressure differential, and crosslinkable groups undergo crosslinking (or coupling). The crosslinking occurs through chemical or physical methods. The high temperature and pressure downhole promote this crosslinking. After crosslinking, the stabilizer loses its stabilizing effect on the latex, leading to latex instability and a phase transition. This fills the fractures and bonds with the formation, achieving intelligent plugging that only occurs when there is leakage. The latex prepolymer acts as a "seed" and "bridging" agent in this process, causing the latex to aggregate and further dehydrate to form a viscous solid barrier, thus completing the plugging process. This technology controls the dehydration and plugging process into two stages: thickening and solidification. This makes it more suitable for well completion and drilling leakage plugging needs that require deep penetration into fractures, rather than just surface or shallow plugging. The plugging material is a polydisperse composite system. When a pressure differential occurs due to leakage, the stabilizer cross-links (or couples), thickening the system but not immediately sealing it. This allows the plugging fluid to continue flowing into and penetrating the fractures, further dehydrating and solidifying during this process, thus avoiding "gate-sealing" of leakage. The plugging material, combined with bridging materials, can seal well losses of different sizes, providing a new intelligent material for well completion and drilling leakage plugging. Unlike previous methods that added salt to latex to cause latex coagulation, this invention avoids the impact of residual cations on the rubber properties after demulsification, providing new ideas and methods for leakage plugging in the drilling field and ensuring safe and efficient operations.

[0016] According to the present invention, preferably, the stabilizer is a polymer, and the stabilizer is selected from at least one of acrylamide-2-methylpropanesulfonic acid (AMPS) dispersants, polycarboxylic acid dispersants, sulfonic acid dispersants, boric acid dispersants, and phosphoric acid dispersants, preferably selected from AMPS dispersants and / or polycarboxylic acid dispersants, and the weight average molecular weight of the stabilizer is 10,000-100,000 g / mol, preferably 20,000-50,000 g / mol.

[0017] According to the present invention, the crosslinkable groups and / or coupling groups carried in the macromolecular chain of the stabilizer include, but are not limited to, at least one of unsaturated double or triple bonds, epoxy groups, mercapto groups, amino groups, hydroxyl groups, thio groups, carboxyl groups, ester groups, urea groups, acyl groups, monoalkoxyphenyl groups, benzyl groups, chlorine groups, and siloxy groups, preferably siloxy groups.

[0018] According to the present invention, preferably, the stabilizer is synthesized from monomers containing crosslinkable groups and / or coupling groups, wherein the weight ratio of the monomers containing crosslinkable groups and / or coupling groups to the stabilizer is (0.001-0.5):1, preferably (0.005-0.1):1. That is, in the stabilizer, the proportion of monomers containing crosslinkable groups and / or coupling groups in the macromolecular chain structure of the obtained stabilizer satisfies the above-mentioned limitations.

[0019] In this invention, the stabilizer can be obtained commercially or in-house. For example, AMPS-type dispersants and polycarboxylate dispersants can be prepared by the following methods: Preparation of AMPS-type dispersants: 100 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid are added to 200-600 parts by weight of deionized water and stirred until dissolved; the pH of the system is adjusted to 9-12; the temperature is raised to 30-70℃, and unsaturated acids and their salts and anhydrides are added. The unsaturated acids and their salts and anhydrides include, but are not limited to, those selected from acrylic acid, methacrylic acid, vinyl sulfonic acid, vinyl sulfonate, vinyl phosphoric acid, vinyl phosphate, maleic acid, and maleic anhydride. At least one of itaconic acid, fumaric acid, styrene sulfonate, propylene sulfonate, and hydroxyethyl methacrylate; the mass ratio of 2-acrylamido-2-methylpropanesulfonic acid and unsaturated acid and its salt and anhydride is (20-80):(80-20), preferably (65-75):(35-25), and the mixture is stirred; then the initiator solution and the monomer with crosslinkable groups are slowly added dropwise, wherein the crosslinkable groups and / or coupling groups are selected from at least one of unsaturated bonds, thio groups, carboxyl groups, ester groups, urea groups and siloxy groups, preferably siloxy groups. The monomer with crosslinkable and / or coupling groups is selected from at least one of vinyltriethoxysilane, vinyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane; the initiator includes peroxide initiators, azo initiators, and redox initiators, preferably at least one of persulfate initiators, persulfate-sulfite systems, and hydrogen peroxide-ascorbic acid systems; the amount of the initiator is 0.1%-1% of the total weight of 2-acrylamido-2-methylpropanesulfonic acid and unsaturated acids and their salts and anhydrides; the weight concentration of the initiator solution is 5%-20%; the temperature is slowly raised to 50-80°C during dropwise addition, and the reaction continues for 2-6 hours after the dropwise addition is completed to obtain the product.

[0020] Preparation of polycarboxylic acid dispersant: comprising 100 parts of unsaturated polyether monomer; 4-40 parts of unsaturated acid or its salt or its anhydride; 0.5-8.5 parts of silane coupling agent; 0.5-1.5 parts of oxidant; 0.25-0.7 parts of reducing agent; and 0.2-1 parts of chain transfer agent. The unsaturated polyether monomer is selected from at least one of methyl allyl alcohol polyoxyethylene / polyoxypropylene ether, isopentenyl alcohol polyoxyethylene ether, and isobutylenyl alcohol polyoxyethylene ether, preferably isopentenyl alcohol polyoxyethylene ether (TPEG); the unsaturated acid or its salt or anhydride monomer is selected from at least one of acrylic acid, methacrylic acid, vinyl sulfonic acid, vinyl sulfonic acid, vinyl phosphoric acid, maleic acid, maleic anhydride, itaconic acid, fumaric acid, 2-acrylamido-2-methylpropanesulfonic acid, styrene sulfonic acid, and propylene sulfonic acid. The preferred silane coupling agent is acrylic acid and itaconic acid; the silane coupling agent is selected from commonly used silane coupling agents in the art, preferably from at least one of vinyltriethoxysilane (A151), vinyltrimethoxysilane (A171), vinyltris(β-methoxyethoxy)silane (A172), γ-aminopropyltriethoxysilane (KH550), γ-glycidoxypropyltrimethoxysilane (KH560), and γ-methacryloyloxypropyltrimethoxysilane (KH570), with KH570 being preferred. The oxidizing agent is selected from at least one of hydrogen peroxide, peracetic acid, and persulfate, with hydrogen peroxide (30% concentration) being preferred; the reducing agent is at least one of ascorbic acid, formaldehyde-sulfuric acid, and sodium dithionite, with ascorbic acid being preferred. The chain transfer agent is at least one of mercaptoacetic acid and mercaptopropionic acid, with mercaptopropionic acid being preferred. Preparation method: (1) Add 100 parts of unsaturated polyether monomer and 150 parts of deionized water to the reactor and stir thoroughly; (2) Start heating, raise the temperature to 50-70℃ and maintain the temperature until the reaction is finished; (3) Add the oxidant to 5 times the amount of deionized water, stir well and then add it to the reactor; (4) Prepare a mixed aqueous solution of reducing agent and chain transfer agent: add the chain transfer agent and reducing agent to 10 times the amount of deionized water and stir thoroughly to dissolve; (5) Prepare an aqueous solution of unsaturated acid or its salt or its anhydride: add the unsaturated acid or its salt or its anhydride to 1 times the amount of deionized water; (6) Add the aqueous solution of unsaturated acid or its salt or its anhydride, silane coupling agent and the mixed aqueous solution of reducing agent and chain transfer agent at the same time according to the required rate; the first two materials are added for 2-4 hours, and the mixed aqueous solution of reducing agent and chain transfer agent is added for 2.5-4.5 hours; (7) After the addition is completed, continue to keep warm and stir for 0.5-1 hours to obtain the final product.

[0021] According to the present invention, preferably, the latex is selected from at least one of nitrile latex, styrene-butadiene latex, styrene-acrylic latex, butyl latex, pure acrylic latex, chloroprene latex, natural rubber latex, fluororubber latex, polybutadiene latex, ethylene propylene diene monomer (EPDM) latex, silicone rubber latex, and polyacrylate latex, and more preferably selected from styrene-acrylic latex.

[0022] Preferably, the average particle size of the latex is 50nm-50μm, and more preferably 100nm-5μm.

[0023] According to the present invention, preferably, the latex prepolymer is a latex with particle size distribution characteristics, that is, it has a certain range of different particle size distributions, with an average particle size range of 200nm-2000μm, preferably 500nm-1000μm.

[0024] Latex prepolymers act as "seeds" and "bridging" agents, enabling latex to aggregate. Limiting the particle size of latex prepolymers to this range allows for better aggregation of the latex. If the particle size is too small, it cannot act as a seed or bridge, while if the particle size is too large, it is detrimental to the stability of the sealing material system.

[0025] In this invention, the latex prepolymer is an aggregate of latex, which can be large-sized latex particles obtained by adding an agglomerating agent to the latex. The agglomerating agent and the latex prepolymer can be prepared by the following methods: Preparation of agglomerating agent: According to the weight parts, add 20-40 parts of olefin monomer (such as butyl acrylate), an appropriate amount of initiator (such as potassium persulfate), and an appropriate amount of emulsifier (such as sodium dodecylbenzene sulfonate) to the reactor; add dropwise a solution composed of 60-80 parts of olefin monomer, α,β-unsaturated carboxylic acid (such as methacrylic acid), initiator (such as potassium persulfate), and distilled water to the reactor, stir and heat, wherein the mass ratio of α,β-unsaturated carboxylic acid to olefin monomer is (3:97)-(30:70), preferably (10:90)-(20:80); the temperature is 50-90℃, preferably 70-80℃; the stirring time is 4-9h, preferably 6-8h, to obtain the agglomerating agent.

[0026] Preparation of latex prepolymer: The agglomerating agent is added to the latex under rapid stirring. The pH of the system is adjusted to 9-10 using sodium hydroxide. After the addition is complete, the stirring is slowed down. The mass ratio of agglomerating agent to latex is (0.5-3):100. The reaction time is 0.5-2 h and the reaction temperature is 30-50℃ to obtain the latex prepolymer of the corresponding latex.

[0027] The latex used to prepare the latex prepolymer can be the latex described in this invention, wherein the latex prepolymer is prepared from at least one selected from nitrile latex, styrene-butadiene latex, styrene-acrylic latex, butyl latex, pure acrylic latex, chloroprene latex, natural rubber latex, fluororubber latex, polybutadiene latex, ethylene propylene diene monomer (EPDM) latex, silicone rubber latex, and polyacrylate latex.

[0028] In this invention, the latex and latex prepolymer contained in the sealing material can be derived from the same or different substances. For example, the latex can be styrene-acrylic latex, but the latex prepolymer can be ethylene propylene diene monomer (EPDM) latex prepolymer. Preferably, the latex and latex prepolymer contained in the sealing material can be derived from the same substance; for example, the latex can be styrene-acrylic latex, and the latex prepolymer can be styrene-acrylic latex prepolymer.

[0029] According to the present invention, preferably, the surfactant is selected from at least one of anionic surfactants, cationic surfactants, amphoteric surfactants and nonionic surfactants; more preferably, it is anionic surfactants and / or nonionic surfactants.

[0030] Preferably, the anionic surfactant is selected from at least one of polyacrylamide, alkylbenzene sulfonate, alkylphenol polyoxyethylene ether ammonium sulfate, fatty acid sulfonyl ester, alkyl sulfonate salt, alkyl sulfonate, polysiloxane, α-alkenyl sulfonate and alkylolamide, preferably alkylphenol polyoxyethylene ether ammonium sulfate, more preferably nonylphenol polyoxyethylene ether ammonium sulfate.

[0031] Preferably, the nonionic surfactant is selected from at least one of alkylphenol polyoxyethylene ether, polyol monofatty acid ester, alkylamine oxide and N-alkylpyrrolidone, preferably alkylphenol polyoxyethylene ether, and more preferably nonylphenol polyoxyethylene ether.

[0032] According to the present invention, preferably, the sealing material comprises the following components in parts by weight: 10-100 parts latex, 1-50 parts latex prepolymer, 0.1-20 parts surfactant, 0.1-10 parts stabilizer, and 10-200 parts water. The present invention limits each component to these ranges, allowing them to work well together and achieve a good sealing effect.

[0033] More preferably, the sealing material comprises the following components in parts by weight: 20-50 parts latex, 10-20 parts latex prepolymer, 5-10 parts surfactant, 2-5 parts stabilizer, and 50-150 parts water.

[0034] In this invention, the sealing material is a stable latex and / or latex prepolymer suspension, wherein the suspended particles have a particle size range of 50nm-2000μm, preferably 100nm-1000μm.

[0035] A second aspect of the present invention provides a method for preparing a leak-sealing material provided by the present invention. The method includes: first mixing latex, surfactant and water, then mixing with a stabilizer, and finally mixing with a latex prepolymer to obtain the leak-sealing material.

[0036] In the preparation method provided by the present invention, the first mixing, the second mixing and the third mixing may involve adding the latex and the surfactant to water, then adding a stabilizer, and finally adding the latex prepolymer.

[0037] The third aspect of the present invention provides the application of the plugging material provided by the present invention or the plugging material prepared by the preparation method provided by the present invention in oil reservoir plugging.

[0038] Preparation Example 1 The stabilizer prepared in this example is a polycarboxylic acid dispersant with a crosslinkable group of siloxy groups. The reaction synthesis process and the structural formulas of the compounds involved are as follows:

[0039] The specific preparation method is as follows: Add 100 kg of isopentenyl alcohol polyoxyethylene ether (TPEG-2400) and 150 kg of deionized water to a reactor, stir, and heat to 70°C. Add 1.5 kg of hydrogen peroxide to 15 kg of deionized water, stir well, and then add to the reactor. Add 7.5 kg of ascorbic acid and 1 kg of 3-mercaptopropionic acid to 17 kg of deionized water to prepare a mixed aqueous solution of reducing agent and chain transfer agent; add 40 kg of acrylic acid (AA) to 40 kg of deionized water to prepare an acrylic acid aqueous solution; simultaneously add the mixed aqueous solution of reducing agent and chain transfer agent, 0.5 kg of silane coupling agent (KH-570), and the acrylic acid (AA) aqueous solution dropwise to a round-bottom flask. Use a peristaltic pump to control the addition of the AA aqueous solution and KH-570 over 4 hours, and the addition of the mixed aqueous solution of ascorbic acid and 1 kg of 3-mercaptopropionic acid over 4.5 hours. After all materials have been added, continue to heat and stir for 0.5 hours to obtain stabilizer sample 1. The weight ratio of the monomer containing cross-linking groups, namely KH570, to the synthesized stabilizer macromolecule is 0.005:1.

[0040] Preparation Example 2 The stabilizer prepared in this example is an AMPS-type dispersant with a siloxy group that can crosslink. The reaction synthesis process and the structural formulas of the compounds involved are as follows:

[0041] The specific preparation method is as follows: 100 kg of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) was added to 200 kg of deionized water and stirred until dissolved; the pH of the system was adjusted to 10; the temperature was raised to 65 °C, and 37 kg of itaconic acid was added and stirred until homogeneous; simultaneously, 17 kg of a 10% (w / w) azobisisobutyramidine hydrochloride initiator solution and 15 kg of γ-glycidoxypropyltrimethoxysilane (KH560) were added dropwise; the temperature was slowly raised to 75 °C during the dropwise addition, and the reaction was continued for 4 h after the addition was completed to obtain stabilizer sample 2. The weight ratio of the monomer containing the crosslinking group, KH560, to the synthesized stabilizer macromolecule was 0.01:1.

[0042] Preparation Example 3 The stabilizer prepared in this example is a boric acid dispersant with a siloxy group that can crosslink. The reaction synthesis process and the structural formula of the compounds involved are as follows:

[0043] The specific preparation method is as follows: the molar ratio of TPEG, 4-vinylphenylboronic acid, AMPS, and vinyltriacetoxysilane is 1:4:5:0.2. Weigh 60g of N-methylpyrrolidone and 50g of TPEG, dissolve and mix them, then pour the mixture into a three-necked flask in a constant temperature water bath. Stir the mixture at a constant speed of 200rpm and heat to 70℃. Weigh 0.70g of azobisisobutyronitrile and dissolve it in 20g of N-methylpyrrolidone, mixing thoroughly to prepare solution A. Weigh 12g of 4-vinylphenylboronic acid, 22g of AMPS, and 1g of vinyltriacetoxysilane and dissolve them in 55g of N-methylpyrrolidone, mixing thoroughly to prepare solution B. Add solutions A and B dropwise to the three-necked flask at a uniform rate using a peristaltic pump over a period of 2 hours. After the addition is complete, maintain the temperature at 60℃ for 2 hours, and add 60g of water dropwise at a uniform rate over these 2 hours. After the reaction was complete, the pH of the polymer was adjusted to 9 to obtain stabilizer sample 3. The weight ratio of the monomer containing the crosslinking group, namely vinyltriacetoxysilane, to the synthesized stabilizer macromolecule was 0.01:1.

[0044] Preparation Example 4 The preparation method is the same as in Preparation Example 1, except that the silane coupling agent KH570 is not added, and stabilizer sample 4 is obtained.

[0045] Preparation Example 5 Preparation of latex prepolymer: Preparation of agglomerating agent sample 1: Add 40 parts butyl acrylate, 0.02 parts sodium persulfate, and 2 parts sodium dodecylbenzenesulfonate to a reaction vessel and stir until the temperature reaches 70°C; then add dropwise a solution composed of 80 parts butyl acrylate, 30 parts methacrylic acid, 0.06 parts sodium persulfate, and distilled water to the reaction vessel; stir for 6 hours. Agglomerating agent sample 1 is then obtained.

[0046] Preparation of latex prepolymer sample 1: Add 3 parts of agglomerant sample 1 to 100 parts of styrene-acrylic latex under rapid stirring. Adjust the pH of the system to 9 using sodium hydroxide. After the addition is complete, slow down the stirring and heat the mixture to 50°C. The reaction time is 2 hours to obtain styrene-acrylic latex prepolymer sample 1.

[0047] Preparation Example 6 The specific preparation methods of the plugging materials in each embodiment and comparative example are as follows: Add latex, surfactant, and water to a reactor in the specified proportions and stir for 30 minutes. Then add stabilizer and stir for 15 minutes. Finally, add latex prepolymer and stir for 15 minutes to prepare a leak-sealing material sample.

[0048] Example 1 Using stabilizer sample 1 from Preparation Example 1, leak-sealing material sample 1 was prepared according to the following raw material composition and the method of Preparation Example 6: Raw material composition: Sample 1: Latex prepolymer of 20 kg styrene-acrylic latex, 5 g surfactant OP-10, 50 kg water, 2 kg stabilizer and 10 kg styrene-acrylic latex.

[0049] Example 2 The preparation method is the same as in Example 1, except that the stabilizer used is the stabilizer sample 2 from Preparation Example 2, and the leak-sealing material sample 2 is obtained.

[0050] Example 3 The preparation method is the same as in Example 1, except that the stabilizer used is the stabilizer sample 3 from Preparation Example 3, and the leak-sealing material sample 3 is obtained.

[0051] Example 4 The preparation method is the same as in Example 1, except that the stabilizer used is the stabilizer sample 4 from Preparation Example 4, and the leak-sealing material sample 4 is obtained.

[0052] Example 5 The preparation method of Example 1 was followed, except that the raw material composition ratio was different, as follows: 20 kg of styrene-acrylic latex emulsion, 5 g of surfactant OP-10, 30 kg of water, 20 kg of stabilizer sample 1, and 10 kg of styrene-acrylic latex prepolymer sample 1. A sealing material sample 5 was obtained.

[0053] Comparative Example 1 The preparation method is the same as in Example 1, except that no latex prepolymer is added.

[0054] Comparative Example 2 The preparation method is the same as in Example 1, except that no stabilizer is added.

[0055] Comparative Example 3 The preparation method is the same as that of Comparative Example 1, except that silane coupling agent KH570 is added instead of polycarboxylic acid dispersant as a stabilizer.

[0056] Test Example 1: Sealing Performance of Leak-Plugging Materials Test method: 500 mL of quartz sand was filled into a high-temperature, high-pressure sand bed simulated leak-sealing instrument. 2 kg of leak-sealing material sample was added to the instrument, and the heating device was turned on to heat the entire instrument to 90°C. Pressure was applied starting from the top of the instrument, beginning with 1 MPa and increasing by 1 MPa each time, up to 12 MPa. At each pressure level, dripping or no leakage was maintained for 30 minutes, after which the pressure was increased by 1 MPa. The data on the sand bed sealing effects of Examples 1-5 and Comparative Examples 1-3 are shown in Table 1.

[0057] Table 1

[0058] As shown in Table 1, the plugging materials of Examples 1-3 of this invention have a good sealing effect on sand beds, can withstand pressure greater than 12 MPa at 90°C, and have similar leakage rates. Example 4 used polycarboxylic acid dispersant without silane coupling agent KH570 as a stabilizer during synthesis, i.e., it has no crosslinking groups, and its pressure resistance at 90°C is only 3 MPa, resulting in a large leakage rate, making it unsuitable for drilling plugging. In Example 5, the amount of stabilizer added was 5 times that of Example 1, but the plugging effect was comparable, indicating that the effect of the stabilizer has a saturation value within a certain range. The plugging material obtained by Comparative Example 1 without the addition of latex prepolymer had a huge leakage rate and could not achieve a sealing effect. The plugging material obtained by Comparative Example 2 using stabilizer without dispersant also had a huge leakage rate and could not achieve a sealing effect. The plugging material obtained by Comparative Example 3 using silane coupling agent KH-570 instead of polycarboxylic acid dispersant as a stabilizer resulted in precipitation of styrene-acrylic latex prepolymer, leading to a huge leakage rate in the plugging experiment and rendering it ineffective for sealing.

[0059] Test Example 2: Sealing performance of plugging material in combination with bridging material Test method: 1 kg of 40-mesh walnut shells and 500 g of 5 mm fiber were added to a 20 kg sample of plugging material and stirred for 15 min to prepare a plugging slurry sample. A 1 mm sealing plate module was then installed in a high-temperature, high-pressure crack simulation plugging instrument, and 2 kg of plugging slurry was added to the simulated wellbore. The heating device was then turned on, heating the entire instrument to 100°C. Pressure was applied starting from the top of the instrument, beginning with 1 MPa and increasing to a maximum of 12 MPa. At each pressure level, dripping or no leakage was maintained for 30 min, after which the pressure was increased by 1 MPa. The plugging effect data of Examples 1-5 and Comparative Examples 1-3 using bridging materials on the 1 mm sealing plate module are shown in Table 2.

[0060] Table 2

[0061] As can be seen from the results in Table 1, the plugging materials of Examples 1-3 and 5 of this invention, in combination with bridging, have a good sealing effect on 1mm cracks, can withstand pressure greater than 12MPa at 100℃, and have similar leakage rates; Example 4 has a pressure resistance of only 4MPa, a large leakage rate, and is not suitable for well drilling plugging; Comparative Examples 1-3 have huge leakage rates and cannot play a sealing role.

[0062] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A leak-sealing material, characterized in that, The sealing material comprises the following components: latex, latex prepolymer, surfactant, stabilizer and water, wherein the stabilizer is a polymer with crosslinkable groups and / or coupling groups, and the stabilizer is selected from acrylamide-2-methylpropanesulfonate dispersants and / or polycarboxylic acid dispersants. The monomer providing the crosslinkable group and / or coupling group is selected from at least one of vinyltriethoxysilane, vinyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane. The latex prepolymer is an aggregate of latex, and the average particle size of the latex prepolymer is 200nm-2000μm.

2. The sealing material according to claim 1, characterized in that, The weight ratio of the monomer providing the crosslinkable group and / or coupling group to the stabilizer is (0.001-0.5):1; and / or The weight-average molecular weight of the stabilizer is 10,000-100,000 g / mol.

3. The sealing material according to claim 2, characterized in that, The weight ratio of the monomer providing the crosslinkable group and / or coupling group to the stabilizer is (0.005-0.1):1; and / or The weight-average molecular weight of the stabilizer is 20,000-50,000 g / mol.

4. The sealing material according to any one of claims 1-3, characterized in that, The sealing material contains the following components in parts by weight: 10-100 parts latex, 1-50 parts latex prepolymer, 0.1-20 parts surfactant, 0.1-10 parts stabilizer, and 10-200 parts water.

5. The sealing material according to claim 4, characterized in that, The sealing material contains the following components in parts by weight: 20-50 parts latex, 10-20 parts latex prepolymer, 5-10 parts surfactant, 2-5 parts stabilizer, and 50-150 parts water.

6. The sealing material according to any one of claims 1-3 and 5, characterized in that, The latex is selected from at least one of nitrile latex, styrene-butadiene latex, butyl latex, chloroprene latex, natural rubber latex, fluororubber latex, polybutadiene latex, ethylene propylene diene monomer (EPDM) latex, silicone rubber latex, and polyacrylate latex; and / or The latex prepolymer is prepared from at least one selected from nitrile latex, styrene-butadiene latex, butyl latex, chloroprene latex, natural rubber latex, fluororubber latex, polybutadiene latex, ethylene propylene diene monomer (EPDM) latex, silicone rubber latex, and polyacrylate latex.

7. The sealing material according to any one of claims 1-3 and 5, characterized in that, The latex is selected from at least one of styrene-acrylic latex and pure acrylic latex; and / or The latex prepolymer is prepared from at least one selected from styrene-acrylic latex and pure acrylic latex; and / or The average particle size of the latex is 50nm-50μm.

8. The sealing material according to claim 7, characterized in that, The latex is selected from styrene-acrylic latex; and / or The average particle size of the latex is 100 nm to 5 μm.

9. The sealing material according to claim 4, characterized in that, The latex is selected from at least one of nitrile latex, styrene-butadiene latex, butyl latex, chloroprene latex, natural rubber latex, fluororubber latex, polybutadiene latex, ethylene propylene diene monomer (EPDM) latex, silicone rubber latex, and polyacrylate latex; and / or The latex prepolymer is prepared from at least one selected from nitrile latex, styrene-butadiene latex, butyl latex, chloroprene latex, natural rubber latex, fluororubber latex, polybutadiene latex, ethylene propylene diene monomer (EPDM) latex, silicone rubber latex, and polyacrylate latex.

10. The sealing material according to claim 4, characterized in that, The latex is selected from at least one of styrene-acrylic latex and pure acrylic latex; and / or The latex prepolymer is prepared from at least one selected from styrene-acrylic latex and pure acrylic latex; and / or The average particle size of the latex is 50nm-50μm.

11. The leak-sealing material according to claim 10, characterized in that, The latex is selected from styrene-acrylic latex; and / or The average particle size of the latex is 100 nm to 5 μm.

12. The sealing material according to any one of claims 1-3, 5 and 7-11, characterized in that, The average particle size of the latex prepolymer is 500nm-1000μm.

13. The sealing material according to claim 4, characterized in that, The average particle size of the latex prepolymer is 500nm-1000μm.

14. The sealing material according to claim 6, characterized in that, The average particle size of the latex prepolymer is 500nm-1000μm.

15. The leak-sealing material according to any one of claims 1-3, 5, 7-11, and 13-14, characterized in that, The surfactant is selected from at least one of anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants.

16. The sealing material according to claim 15, characterized in that, The surfactant is an anionic surfactant and / or a nonionic surfactant; and / or The anionic surfactant is selected from at least one of alkylbenzene sulfonates, alkylphenol polyoxyethylene ether ammonium sulfate, fatty acid sulfonyl esters, alkyl sulfonate salts, alkyl sulfonates, and α-alkenyl sulfonates; and / or The nonionic surfactant is selected from at least one of alkylphenol polyoxyethylene ether, polyol monofatty acid ester, alkylamine oxide and N-alkylpyrrolidone.

17. The sealing material according to claim 16, characterized in that, The anionic surfactant is alkylphenol polyoxyethylene ether ammonium sulfate; and / or The nonionic surfactant is alkylphenol polyoxyethylene ether.

18. The leak-sealing material according to claim 17, characterized in that, The anionic surfactant is nonylphenol polyoxyethylene ether ammonium sulfate; and / or The nonionic surfactant is nonylphenol polyoxyethylene ether.

19. The sealing material according to claim 4, characterized in that, The surfactant is selected from at least one of anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants.

20. The sealing material according to claim 19, characterized in that, The surfactant is an anionic surfactant and / or a nonionic surfactant; and / or The anionic surfactant is selected from at least one of alkylbenzene sulfonates, alkylphenol polyoxyethylene ether ammonium sulfate, fatty acid sulfonyl esters, alkyl sulfonate salts, alkyl sulfonates, and α-alkenyl sulfonates; and / or The nonionic surfactant is selected from at least one of alkylphenol polyoxyethylene ether, polyol monofatty acid ester, alkylamine oxide and N-alkylpyrrolidone.

21. The sealing material according to claim 20, characterized in that, The anionic surfactant is alkylphenol polyoxyethylene ether ammonium sulfate; and / or The nonionic surfactant is alkylphenol polyoxyethylene ether.

22. The leak-sealing material according to claim 21, characterized in that, The anionic surfactant is nonylphenol polyoxyethylene ether ammonium sulfate; and / or The nonionic surfactant is nonylphenol polyoxyethylene ether.

23. The sealing material according to claim 6, characterized in that, The surfactant is selected from at least one of anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants.

24. The sealing material according to claim 23, characterized in that, The surfactant is an anionic surfactant and / or a nonionic surfactant; and / or The anionic surfactant is selected from at least one of alkylbenzene sulfonates, alkylphenol polyoxyethylene ether ammonium sulfate, fatty acid sulfonyl esters, alkyl sulfonate salts, alkyl sulfonates, and α-alkenyl sulfonates; and / or The nonionic surfactant is selected from at least one of alkylphenol polyoxyethylene ether, polyol monofatty acid ester, alkylamine oxide and N-alkylpyrrolidone.

25. The leak-sealing material according to claim 24, characterized in that, The anionic surfactant is alkylphenol polyoxyethylene ether ammonium sulfate; and / or The nonionic surfactant is alkylphenol polyoxyethylene ether.

26. The sealing material according to claim 25, characterized in that, The anionic surfactant is nonylphenol polyoxyethylene ether ammonium sulfate; and / or The nonionic surfactant is nonylphenol polyoxyethylene ether.

27. The sealing material according to claim 12, characterized in that, The surfactant is selected from at least one of anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants.

28. The leak-sealing material according to claim 27, characterized in that, The surfactant is an anionic surfactant and / or a nonionic surfactant; and / or The anionic surfactant is selected from at least one of alkylbenzene sulfonates, alkylphenol polyoxyethylene ether ammonium sulfate, fatty acid sulfonyl esters, alkyl sulfonate salts, alkyl sulfonates, and α-alkenyl sulfonates; and / or The nonionic surfactant is selected from at least one of alkylphenol polyoxyethylene ether, polyol monofatty acid ester, alkylamine oxide and N-alkylpyrrolidone.

29. The sealing material according to claim 28, characterized in that, The anionic surfactant is alkylphenol polyoxyethylene ether ammonium sulfate; and / or The nonionic surfactant is alkylphenol polyoxyethylene ether.

30. The sealing material according to claim 29, characterized in that, The anionic surfactant is nonylphenol polyoxyethylene ether ammonium sulfate; and / or The nonionic surfactant is nonylphenol polyoxyethylene ether.

31. A method for preparing a sealing material according to any one of claims 1-30, characterized in that, The preparation method includes: first mixing latex, surfactant and water, then mixing with stabilizer, and finally mixing with latex prepolymer to obtain the sealing material.

32. The application of the plugging material according to any one of claims 1-30 or the plugging material prepared by the preparation method according to claim 31 in reservoir plugging.

Citation Information

Patent Citations

  • Temperature-resistance drilling fluid drill-feeding plugging agent and its preparation method

    CN103937471A

  • Polymer having dispersing function, polycarboxylic acid cement dispersant, preparation method therefor and use thereof

    WO2022078046A1